The Role of Leadership in Developing Digital Information Technology in Elementary Schools on Simeulue Island - Ema Malini; Bahrun Bahrun; Ismail Ismail; Ilmiadin Ilmiadin (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
The rapid advancement of digital information technology has significantly transformed the education sector, requiring elementary schools to adapt to remain relevant in the digital transformation era. This study is important because school principals play a strategic role in directing and optimizing the use of digital technology to enhance instructional quality and school management. The research aims to explore the development of digital information technology in elementary schools and examine its application in learning activities. A qualitative descriptive method was employed, using passive participant observation, semi-structured interviews, and documentation. The study involved 12 participants from SDN 2, SDN 13, and SDN 7 Simeulue, including school principals, learning community teachers, school operators, and supervisors. The findings indicate that principals hold a central role in guiding and motivating teachers to utilize digital tools for both instructional and administrative purposes. Through visionary leadership, principals encourage the integration of digital platforms into daily school activities. However, challenges remain, particularly limited internet connectivity and the fact that some teachers have not fully incorporated digital technology into their teaching practices. The study concludes that the principal’s role is crucial in improving teacher competence and building an effective digital learning ecosystem. This research strengthens the literature on educational leadership in the digital era and provides practical recommendations, including continuous digital training, improved network infrastructure, and consistent digital-based management policies. Further research is recommended to evaluate the long-term effectiveness of digital training programs and their impact on classroom practices.